Application of metagenomic next-generation sequencing in the diagnosis and treatment of recurrent urinary tract infection in kidney transplant recipients - Duan, Wenjing; Yang, Yongguang; Zhao, Jingge; Yan, Tianzhong; Tian, Xiangyong (Frontiers in Public Health, 2022)
BACKGROUND: Rapid and accurate pathogen diagnosis is an urgent unmet clinical need for recurrent urinary tract infection (RUTI) in kidney transplant recipients (KTRs). Metagenomic next-generation sequencing (mNGS) may offer another strategy for diagnosing uropathogens but remains to be studied. METHODS: Nineteen KTRs with RUTI were collected in this study. The uropathogens were detected and compared by mNGS and urine culture, respectively. Modifications of the anti-infection strategy were also assessed. RESULTS: Rich and diverse pathogens were revealed by mNGS. mNGS was significantly higher than culture in total positive rate (100.00% vs 31.6%; P < 0.01), and in identification rates for bacteria (89.5% vs 31.6%; P < 0.01), for viruses (57.9% vs 0; P < 0.01) and for fungi (42.1% vs 0; P < 0.01), respectively. mNGS identified a significantly higher proportion of mixed infections than culture (89.5% vs 10.5%; P＜0.01). The anti-infection therapies were adjusted in 2 (33.3%) and 12 (76.9%) cases guided by culture and mNGS respectively. CONCLUSION: mNGS has more remarkable etiological diagnostic performance compared with urine culture for KTRs with RUTI to guide anti-infection strategies and, in turn, protect the graft.